A legal analysis on money laundering in the football industries of the United States of America, England and Malaysia - Dhillon, Guru (2014)
This study is a legal analysis on money laundering activities in the football industries of the United States of America, England and Malaysia. Firstly, the problems that surfaced were that there is no up to date information on the current levels of money laundering instances in the targeted football industries. Secondly, there are no specific provisions in the general Anti-Money Laundering Laws and Football Regulations governing money laundering in the targeted football industries. Thirdly, the enforcement mechanisms regulating the football industry appear ineffective as the targeted football industries have been somewhat spared from any money laundering prosecutions. This study examined the prevalence of money laundering, determined the effectiveness of the general Anti-Money Laundering Laws and Football Regulations and the accompanying enforcement mechanisms in the targeted football industries. Money laundering typologies and case studies from Football Clubs were highlighted and analyzed. All relevant Conventions, Treaties, Anti-Money Laundering Laws, Football Regulations, the Financial Action Task Force (FATF) 40 +9 Recommendations and the latest FATF 2012 Recommendations have been thoroughly examined. Relevant reports by various organizations were inspected and apt conclusions were highlighted. Interviews with money laundering experts were also conducted to supplement the general findings. It was found that money laundering is prevalent in the targeted football industries, the general Anti- Money Laundering Laws and Football Regulations as well as the enforcement mechanisms are ineffective in regulating money laundering activities in the targeted football industries. It has been recommended that various types of reforms be implemented by the authorities of the United States of America, England and Malaysia to curtail money laundering activities in their respective football industries. Such recommendations include the adoption of the Indian Cricket Anti-Corruption Code, adopting certain provisions from The Argentina Money Laundering Regulations regulating the football industry of Argentina and to strengthen enforcement mechanisms on online betting. All the Research Questions were successfully answered and all the objectives set at the beginning of the research have been met.